2002
DOI: 10.1074/jbc.m108730200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Regulates Stearoyl Coenzyme A Desaturase Expression through a Smad Signaling Pathway

Abstract: The regulation of stearoyl-CoA desaturase (SCD), a rate-limiting enzyme in the synthesis of unsaturated fatty acids, is physiologically important because the ratio of saturated to unsaturated fatty acids is thought to control cellular functions by modulating the structural integrity and fluidity of cell membranes. Transforming growth factor-␤ (TGF-␤), a multifunctional cytokine, increased SCD mRNA expression in cultured human retinal pigment epithelial cells. This response was elicited by all three TGF-␤ isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 70 publications
(66 reference statements)
3
30
0
Order By: Relevance
“…Our finding that increasing ∆9-desaturase mRNA concentrations are higher than the corresponding ∆9-desaturase enzyme activities are well in line with previous results [32,33]. The differences could be explained by the fact that the half-life of ∆9-desaturase is very short [32] thus rapid changes of mRNA levels are not equivalently translated into a corresponding increase in ∆9-desaturase enzyme activity.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that increasing ∆9-desaturase mRNA concentrations are higher than the corresponding ∆9-desaturase enzyme activities are well in line with previous results [32,33]. The differences could be explained by the fact that the half-life of ∆9-desaturase is very short [32] thus rapid changes of mRNA levels are not equivalently translated into a corresponding increase in ∆9-desaturase enzyme activity.…”
Section: Discussionsupporting
confidence: 91%
“…More interestingly, it was also observed that the expression of SCD, SMAD3 and CYB5R3 was lower in the mammary gland of Defective genotype goats (Table 1). SMAD3 encodes a protein that belongs to a large family known as cytoplasmic mediators, which regulate the transcription of target genes (Heldin et al, 1997), including the SCD gene (Samuel et al, 2002). Moreover, stearoyl-CoA desaturase (encoded by the SCD gene) and NADHcytochrome b5 reductase (encoded by the CYB5R3 gene) are components of a FA-desaturase system directing the synthesis of D-9 unsaturated FA.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, TGFBI was also found to be overexpressed in lung cancer and was correlated with later stages of lung cancer (Sasaki et al, 2002). SCD can be induced by TGF-b1, 2 or 3 in cultured human retinal pigment epithelial cells (Samuel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%